A Study on Gender Justice and Enforcement of Law (Journal of Advances and Scholarly Researches in Allied Education, 2024)
This research looks at the real-life problems women have when trying to get legal help and how gender justice laws are really enforced. Despite the existence of many laws meant to safeguard women against assault and discrimination based on their gender, there are still gaps in their implementation caused by institutional, social, and cultural obstacles. To evaluate the efficacy of these legislation, the research used a mixed-method approach, integrating quantitative survey data with qualitative interview insights. The results show that women aren't aware of the problem, that law enforcement isn't effective, and that patriarchal traditions are a major obstacle to justice. Additionally, the study underscores the compounded discrimination faced by marginalized groups, emphasizing the need for an intersectional approach to gender justice. Recommendations are provided to improve legal awareness, strengthen institutional responses, and enhance support for victims.